Towards Shared Social Responsibility: A Study of Consumers’ Willingness to Donate Micro-Insurances when Taking Out Their Own Insurance - Jansen, Patty; Gößling, Tobias 1970-; Bullens, Toon (2011)
In recent years, the concepts of charity and development aid have changed significantly. Present concepts combine direct money transfer with co-production, knowledge sharing and the development of products and services designed for the need of developing and transition economies. The concept of micro-financing is a financial service which has proven to allow for entrepreneurs in the respective countries to start up their businesses. A relatively new financial product for these countries is micro-insurance. This article deals with the question whether consumers in the Netherlands are willing to donate micro-insurances and which factors influence this willingness to contribute to the non-profit micro-insurance approach of an insurance company. The data were collected with questionnaires among a sample of the Dutch population (N = 504). The data have been processed in a one-way between-groups ANOVA, a paired sample t test and an ordinal regression analysis. The results show that approximately half of the Dutch consumers are willing to pay an additional amount on their insurance premium for the donation of micro-insurances. The amount of the insurance premium did, however, not affect the willingness to donate (WTD). If consumers could choose the beneficiary less people are willing to donate, yet those people are willing to donate more money. In conclusion, there is readiness among consumers to contribute to micro-insurance via an insurance company that assists in setting up micro-insurance projects. This indicates a possible role for companies to act as an intermediary between philanthropic acts and consumers.
Keywords: willingness to donate; micro-insurance; Corporate Social Responsibility; Consumer Behaviour